Expanding Opportunities: Scaling Up Gender and Social Inclusion in AICCRA - Huyer, Sophia; Simelton, Elizabeth; Chanana, Nitya; Mulema, Annet A; Marty, Edwige (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The framework presented here integrates CGIAR and AICCRA experience in gender and socially-inclusive approaches to reach women, youth and under-represented groups, to develop a model for scaling up climate resilient agriculture that integrates equality and empowerment.